The ‘Archeology’ of historiography as a rhetorical agon. On the juxtaposition of hellenic writers in the Epistula ad Pompeium by Dionysius of Halicarnassus - Sinitsyn, Aleksandr (Acta Archaeologica Lodziensia, 2021)
Dionysius of Halicarnassus in his short theoretical treatise entitled “A Letter to Pompeius” (Epistula ad Pompeium) presents an exciting discussion on rhetoric mastership and scholarship written in an epistolary genre. The treatise begins with critical remarks Dionysius once addressed to Plato. The author admits to his addressee (Cn. Pompeius Geminus) that he is enchanted by Plato’s dialogues. From the trio of Greek speech-makers who are recognized as the most brilliant in this respect – Isocrates, Plato, and Demosthenes (such was Dionysius’s selection) – the Halicarnassean rhetorician deliberately dwells on Plato (Lysias, Isocrates, Demosthenes and other Greek orators are the subject of his other aesthetic works). Embarking on a wider discussion, Dionysius repeatedly points out that these studies are always aimed at establishing the truth. The longest chapter, 3 compares works of the first Greek historians and the mastery of their style. Dionysius points out the rivalry of the many masters of the genre, but the main characters of the chapter are Herodotus and Thucydides. The “father of history” (Dionysius’ contemporary and paragon) surpasses the Athenian historian on all counts examined by the author. This article examines συγγραφεύς / συγγραφεῖς or συγγραφή occurring in the Pomp. by Dionysius of Halicarnassus. The rhetorician, when referring to Herodotus, Thucydides (ch. 3), Theopompus (ch. 6), Hellanicus, Charon (3.7) and the Greek historians en masse (6.7), calls them “syngraphers”. Dionysius uses the word συγγραφή only as applied to historical works of Theopompus of Chios (6.2, 3, 6). The article also draws upon the Halicarnassian philologist’s other works in which he mentions syngraphers-historians, who are set off against poets and orators. Dionysius regards the words συγγραφεύς, ὁ ἱστορικός, ἱστοριογράφος as equivalent and interchangeable. In this work, Dionysius examines different styles of ancient writers. Here, by examining the works by the authors of the 5th and 4th centuries BC (written three to four centuries before his time) he seems to be performing a peculiar experiment of theoretical “archaeology”. But the rhetoric and philological “archaeological” study conducted by Dionysius of Halicarnassus reveals not only his scholarly interest in the analysis of works of the writers of the past, but also his focus on the present – both in literary and cultural aspects. Plato is under the influence of Thucydides, but Thucydides is inferior to Herodotus, Herodotus produces works that surpass those of Charon and Hellanicus, while Theopompus is superior in style to Demosthenes himself and surpasses Isocrates – the “most brilliant” rhetoricians of the past. By presenting this gallery of names, Dionysius shows comparison as agon – of styles, genres, authors, their subject matters, intensive narrative, and he himself contends with the writers of the past. Seeing mastery of rhetoric as a peculiar agon stretching over centuries and across the agon of rhetoricians, philosophers and historiographers, Dionysius identifies the circle of best writers, and himself joins it. He claims that in the scholarly rhetoric “the truth is dearer still” and establishes the criteria to judge the classic writers. And the critic realizes that he will be judged according to the same (his own) criteria